Intertextuality reception in postmodernist discourse - Bezrukov, Andrey N. (Przegląd Wschodnioeuropejski, 2018)
The main study subject of the article is intertextual postmodern text interaction with the legacy of Russian classics of XIX–XX centuries. A cultural dialogue being a semantic point of convergence of the text factual and ideological levels is in the focus of investigation. The purpose of the research undertaken is observation of the postmodern artistic unity transformational nature, represented by the projection of systemic/non-systemic writing/ /reading. Methodologically, the work is based on the receptive approach to identification of individual features of the text and its semantic correlates. The analysis allowed us to direct attention to intertextual variations, discursive imagery circumvolutions, presence of parallel and reverse vectors in the newly created texts. The concepts of the intertextual matrix situation put across are illustrated with the fictional examples (Pushkin, Dostoevsky, Yerofeyev). The article is intended (field of application) for the Russian and foreign researchers of the postmodern discourse, intertextual communication, literary forms dialogue, signimic level text transformed into a semantic construct. The analysis results posit that formal intertextuality character (citation scale) in the individual text concept expands to the phenomenon, bearing convergent characteristics, and the semantic field extension can be carried out with the help of the receptive approach.